2012
DOI: 10.1001/archpediatrics.2012.1003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Micronutrient Sprinkles on Reducing Anemia

Abstract: To evaluate the effectiveness of Sprinkles alongside infant and young child feeding (IYCF) education compared with IYCF education alone on anemia, deficiencies in iron, vitamin A, and zinc, and growth in Cambodian infants.Design: Cluster-randomized effectiveness study.Setting: Cambodian rural health district.Participants: Among 3112 infants aged 6 months, a random subsample (n = 1350) was surveyed at baseline and 6-month intervals to age 24 months.Intervention: Daily micronutrient Sprinkles alongside IYCF educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 27 publications
6
68
2
5
Order By: Relevance
“…On average, children consumed between 96% 8 and 75% of the sachets. 2,9,16 We found that the prevalence of vitamin A deficiency was similar at baseline and follow-up. These findings are similar to those of three other studies of home fortification products in which there was no significant impact of the intervention on vitamin A status.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…On average, children consumed between 96% 8 and 75% of the sachets. 2,9,16 We found that the prevalence of vitamin A deficiency was similar at baseline and follow-up. These findings are similar to those of three other studies of home fortification products in which there was no significant impact of the intervention on vitamin A status.…”
Section: Discussionmentioning
confidence: 67%
“…In a cluster randomized trial of children 6-11 months in Cambodia conducted by Jack et al, children were assigned to either a treatment group that received both IYCN and MNP sachets (12.5 mg iron) or a control group that received IYCN alone. 9 At 12 months, compared with the control group, children in the treatment group showed a 20.6-PP reduction in anemia (84.7% vs 66.7%, P<0.001). In a series of cross-sectional surveys conducted in Bhutanese refugee children living in camps in Nepal, Bilukha assessed the anemia status of children 13 months before and at 26 months after distribution of MNP sachets (10 mg iron), which were to be consumed every other day.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations